Why does fiscal decentralization negatively affect student dropout rates? Results from Indonesia’s National Socioeconomic Survey 2002-2014 and two case studies - Pujiastuti, Reni Tri; Sujarwoto, Sujarwoto (FIA UB, 2017)
The consequences of fiscal decentralization on basic education outcomes are always debatable. Yet, its consequences on student dropout rates remain questionable. In this paper, we examine why fiscal decentralization in Indonesia has not effectively reduced student dropout. Mixed method analyses combining the Indonesian National Socioeconomic Survey (Susenas) 2002-2014 and two case studies in the districts of Sleman and Yogyakarta are used to explore the reasons for which fiscal decentralization has not reduced student dropout in Indonesia. Instead of reducing student dropout, we found that fiscal decentralization increases the risk of student dropout at the elementary school, transitional and junior secondary school levels. We found lack of fiscal capacity, inefficiency of educational budget allocation, and technical inefficiency in program implementation to be the main challenges that prevent district governments from effectively reducing student dropout.